Influence of active cooling on microstructure and mechanical properties of wire arc additively manufactured mild steel - Dash, Aruntapan; Squires, Lile; Avila, Jose D.; Bose, Susmita; Bandyopadhyay, Amit (Frontiers in Mechanical Engineering, 2023)
Additive manufacturing (AM) of metals attracts attention because it can produce complex structures in a single step without part-specific tooling. Wire arc additive manufacturing (WAAM), a welding-based method that deposits metal layer by layer, is gaining popularity due to its low cost of operation, feasibility for large-scale part fabrication, and ease of operation. This article presents the fabrication of cylindricalshaped mild steel (ER70S-6) samples with a gas metal arc (MIG)—based hybrid WAAM system. A mechanism for actively cooling the substrate is implemented. Deposition parameters are held constant to evaluate the impact of active cooling on deposition quality, inter-pass cooling time, and internal defects. Surface and volume defects can be seen on the cylindrical sample fabricated without an active cooling setup. Defect quantification and phase analysis are performed. The primary phase formed was α-iron in all samples. Actively cooled deposition cross section showed a 99% decrease of incomplete fusion or porosity, with temperature measured 60 s after deposition averaging 235°C less than non-cooled. Microstructural analysis revealed uniformity along the build direction for actively cooled deposition but non-uniform microstructures without cooling. Hardness decreased by approximately 22HV from the first layer to the final layer in all cases. Property variation can be attributed to the respective processing strategies. The current study has demonstrated that active cooling can reduce production time and porosity while maintaining uniform microstructure along the build direction. Such an approach is expected to enhance the reliability of WAAM-processed parts in the coming days.